2012
DOI: 10.2217/fmb.12.4
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Newcastle Disease Virus for Cancer Therapy: Old Challenges and New Directions

Abstract: Summary Newcastle Disease Virus (NDV) is an avian paramyxovirus, which has been demonstrated to possess significant oncolytic activity against mammalian cancers. This review summarizes the research leading to the elucidation of the mechanisms of NDV-mediated oncolysis as well as the development of novel oncolytic agents through the use of genetic engineering. Clinical trials utilizing NDV strains and NDV-based autologous tumor cell vaccines will expand our knowledge of these novel anti-cancer strategies and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
192
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(203 citation statements)
references
References 168 publications
4
192
0
7
Order By: Relevance
“…However, the fact that the pancreas is not considered a typical replication site for IAVs in humans, the modest replication level displayed by the H7N3 NS1-77 virus in mammalian non-malignant cells together with its administration in a confined space should enhance the safety of the potential treatment. Furthermore, rapid accumulation of virus-neutralizing antibodies in recipients has been reported also in the case of treatment with viruses that normally do not infect humans (Tesfay et al, 2014;Zamarin & Palese, 2012), and indeed one of the biggest challenges for OVs consists in eluding the adaptive immunity that might undermine their efficacy especially in a multi-dose regimen (Miest et al, 2011;Russell et al, 2012).…”
Section: The Immunostimulatory Activity Of H7n3 Ns1-77 Virus In Infecmentioning
confidence: 99%
“…However, the fact that the pancreas is not considered a typical replication site for IAVs in humans, the modest replication level displayed by the H7N3 NS1-77 virus in mammalian non-malignant cells together with its administration in a confined space should enhance the safety of the potential treatment. Furthermore, rapid accumulation of virus-neutralizing antibodies in recipients has been reported also in the case of treatment with viruses that normally do not infect humans (Tesfay et al, 2014;Zamarin & Palese, 2012), and indeed one of the biggest challenges for OVs consists in eluding the adaptive immunity that might undermine their efficacy especially in a multi-dose regimen (Miest et al, 2011;Russell et al, 2012).…”
Section: The Immunostimulatory Activity Of H7n3 Ns1-77 Virus In Infecmentioning
confidence: 99%
“…Currently, there are 600 citations that support the use of NDV in cancer therapy. Zamarin and Palese (2012) have published a very thorough and useful review of this literature.…”
Section: Viral Infection For Cancer Therapymentioning
confidence: 99%
“…Thus, inducing cell death by reducing the level and functionality of Hsps in cancer cells is an attractive strategy for cancer therapy (Galluzzi et al 2006;Jego et al 2010). Zamarin and Palese (2012) noted that virulence of NDV strains in birds correlates directly with their oncolytic properties. We suggest that there is also a direct correlation between the ability of virulent strains to inhibit host protein synthesis-including cellular stress protein synthesis-and the oncolytic properties of NDV.…”
Section: Viral Infection For Cancer Therapymentioning
confidence: 99%
“…The inherent viral oncolytic properties are believed to be derived from defective IFN signaling pathways in tumor cells. 3,5,8 The development of reverse genetics technology for NDV enable us to modify the NDV genome as well as introduce foreign sequences to refine the antitumor activity. [9][10][11][12][13] Previous studies in our laboratory showed that recombinant NDVs (rNDVs) expressing Trail, interleukin (IL) 15, and IL-2 are promising antitumor agents.…”
Section: Introductionmentioning
confidence: 99%